Plasma interface regulated hierarchical corona-resistant polyimide gradient composite film and preparation method thereof

CN122976150APending Publication Date: 2026-10-27HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611172416.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

这些缺陷会诱发空间电荷积聚与局部电场畸变,反而成为电树枝起始与扩展的薄弱环节,导致复合薄膜的绝缘强度劣化

Benefits of technology

为克服现有技术中聚酰亚胺基复合薄膜因界面结合不良、梯度结构突变及浓度配比缺乏定量依据所导致的绝缘性能不足等问题,本发明提供一种聚酰亚胺基复合薄膜及其制备方法,其通过界面强化、缓变梯度结构设计及浓度配比优化,实现了绝缘击穿场强、耐电晕寿命与高温稳定性的协同提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122976150A_ABST
    Figure CN122976150A_ABST
Patent Text Reader

Abstract

The application discloses a kind of plasma interface regulation's hierarchical corona-resistant polyimide gradient composite film and preparation method thereof, belong to electrical insulating material technical field.The application is aimed at the problem of existing gradient corona-resistant film interlayer electric field abrupt change, interface defect is many, concentration ratio lacks system quantitative optimization.The application uses nitrogen low-temperature plasma to modify hexagonal boron nitride, strengthens the interface combination of filler and matrix;Meanwhile, design three-layer symmetric gradient structure, form concentration gradually changing transition zone by layer-by-layer pre-curing, system control obtains four kinds of interlayer mass fraction ratio (1-8-1, 2-6-2, 3-4-3, 4-2-4), constructs "surface layer anti-erosion barrier-transition zone electric field gradually changes-core layer uniform field heat conduction" three-level corona-resistant protection system.4-2-4 obtained film 150 ℃ characteristic breakdown field strength is as high as 510.5 kV / mm, high-frequency pulse under corona-resistant life is as long as 7.3±0.9 minutes, is suitable for new energy automobile drive motor, high-speed traction motor and other high-temperature high-frequency severe working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrical insulation materials. Specifically, it relates to a graded corona-resistant polyimide gradient composite film with plasma interface regulation and its preparation method. It is mainly used in the inter-turn insulation system under high temperature and high frequency conditions, such as drive motors for new energy vehicles, traction motors for high-speed rail transit, and high-frequency power transformers. Background Technology

[0002] When a variable frequency drive system uses pulse width modulation (PWM) technology, the high-frequency pulse voltage with a steep rising edge generated will create overvoltage and local electric field concentration between the turns of the motor winding, thereby inducing continuous corona discharge. Corona discharge is an insulation aging process under the coupled effects of multiple factors such as electricity, heat, and chemistry, which eventually leads to insulation breakdown failure. It is a key technical bottleneck restricting the operational reliability and service life of high-voltage power equipment.

[0003] Polyimide (PI) has become the mainstream matrix material for inter-turn insulation in motors due to its excellent heat resistance, mechanical properties, and insulation performance. However, the corona resistance of pure PI films is insufficient, making it difficult to meet the long-term service requirements under high-voltage and high-frequency operating conditions. To improve its corona resistance, existing technologies typically dope the PI matrix with wide-bandgap inorganic fillers such as hexagonal boron nitride (BN) to form composite films. In addition, some existing studies further employ gradient structure designs to achieve functional partitioning, aiming to overcome the performance dilemma of the trade-off between insulation strength and corona resistance lifetime in monolayer uniform doping.

[0004] However, the aforementioned existing technologies still have the following technical defects: Unmodified BN has low surface chemical activity and insufficient interfacial bonding with the PI matrix, making it prone to interfacial voids and deep-level charge traps. These defects can induce space charge accumulation and local electric field distortion, which in turn become weak links for the initiation and propagation of electrical trees, leading to a deterioration in the insulation strength of the composite film.

[0005] Existing gradient structures mostly adopt a layered stacking method with abrupt concentration changes, resulting in significant differences in dielectric constant between layers. This leads to an electric field concentration effect at the interface, which partially offsets the performance gains that the gradient structure should bring. Furthermore, under high temperature conditions, the dielectric constant mismatch intensifies, resulting in a significant decrease in breakdown field strength.

[0006] For the symmetrical sandwich structure of "surface-core-surface", most existing three-layer gradient studies are still at the qualitative exploration level. The quantitative influence of interlayer concentration gradient on insulation breakdown performance, corona resistance lifetime and high temperature stability is still unclear. There is a lack of systematic optimization schemes, making it difficult to provide reliable data support for engineering selection.

[0007] Therefore, developing a highly insulating and corona-resistant PI-based composite film that combines stable interfacial bonding, uniform internal electric field distribution, and quantifiable optimization of gradient ratio is a technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides a graded corona-resistant polyimide gradient composite film with plasma interface modulation and its preparation method. This invention achieves interface modification of BN filler through nitrogen plasma, combined with a concentration-gradient transition zone formed by layer-by-layer pre-curing. It systematically controls four typical interlayer concentration ratios (1-8-1, 2-6-2, 3-4-3, 4-2-4) to construct a three-level protection system: surface corrosion resistance, transition zone gradual field, and core layer heat homogenization. This reveals the influence of concentration gradient on insulation and corona resistance performance, solving the problems of abrupt interfacial electric field changes, numerous interfacial defects, and ambiguous ratio selection in existing gradient films, achieving a synergistic improvement in insulation strength and corona resistance lifetime.

[0009] To address the aforementioned technical problems, the present invention adopts the following technical solution: The purpose of this invention is to provide a graded corona-resistant polyimide gradient composite film with plasma interface regulation. It has a three-layer symmetrical gradient structure, consisting of an upper surface layer, a core layer, and a lower surface layer tightly bonded together. The upper and lower surface layers have identical composition and thickness, both being polyimide matrices doped with plasma-modified boron nitride. The core layer is also a polyimide matrix doped with plasma-modified boron nitride. The boron nitride mass fraction exhibits a symmetrical gradient distribution along the film thickness direction, and a gradually changing transition region with continuously varying boron nitride concentration is formed between the surface layer and the core layer. The plasma-modified boron nitride is a hexagonal boron nitride nanosheet treated with nitrogen-containing polar groups on its surface, forming a micro / nano rough structure that creates a dual interfacial interaction of physical intercalation and chemical bonding with the polyimide matrix.

[0010] Furthermore, the gradual transition zone is naturally formed by the interdiffusion of polyamic acid molecules between the upper and lower layers during the layer-by-layer pre-curing process, with a thickness of 0.5-2µm, accounting for 5%-10% of the single-layer thickness. The BN concentration in the transition zone changes continuously and gradually, corresponding to no abrupt step in the dielectric constant, which can eliminate the interlayer electric field concentration of traditional abrupt gradient structures. That is, it is used to suppress interlayer electric field concentration, significantly reduce the probability of electric tree initiation at the interface, and at the same time alleviate the internal stress caused by the mismatch of interlayer thermal expansion coefficients.

[0011] Furthermore, the upper and lower surface layers are corona-resistant and corrosion-resistant functional layers with a BN mass fraction of 1wt%-4wt%, specifically 1wt%, 2wt%, 3wt%, and 4wt%. These layers directly withstand corona discharge bombardment: on one hand, the two-dimensional layered structure of the BN nanosheets scatters high-energy charged particles, blocking ozone corrosion; on the other hand, during corona aging, the surface PI gradually degrades, and BN accumulates to form a dense inorganic self-barrier layer, continuously resisting erosion. The overall corona resistance lifetime monotonically increases with increasing surface BN content.

[0012] Furthermore, the core layer serves as an electric field homogenization and thermal conductivity functional layer, with a BN mass fraction of 2-8 wt%, specifically 2 wt%, 4 wt%, 6 wt%, and 8 wt%. The network structure constructed by BN can scatter charge carriers, block the longitudinal expansion of electrical trees, and simultaneously conduct corona heat generation rapidly along the in-plane, suppressing the formation of local hot spots and the risk of thermal breakdown. Higher BN content in the core layer results in greater thermal conductivity potential, but also a larger interlayer concentration gradient, which can easily lead to interfacial stress mismatch.

[0013] Furthermore, the differences in boron nitride mass fraction between the surface layer and the core layer are 1 wt%, 2 wt%, 4 wt%, and 7 wt%, respectively.

[0014] Furthermore, the modified BN is a hexagonal boron nitride nanosheet treated with nitrogen low-temperature plasma, with a sheet diameter of 1μm~5μm. The plasma treatment has the dual effects of physical etching and chemical modification: physically, it etches the surface of the filler to form a micro-nano rough structure, which enhances the mechanical intercalation with the PI matrix; chemically, it introduces nitrogen-containing polar groups such as amino and imino groups on the surface, which can form hydrogen bonds or even chemical bonds with the PI molecular chain, greatly improving the interfacial bonding strength, reducing interfacial void defects, and simultaneously regulating the interfacial trap energy level to suppress the accumulation of space charge.

[0015] As four typical formulation schemes for system optimization, the surface-core-surface mass fraction ratios are 1-8-1, 2-6-2, 3-4-3, and 4-2-4, respectively: Among them, the 1-8-1 mix has the highest BN content in the core layer (8 wt%) and the lowest in the surface layer (1 wt%), with the largest interlayer gradient. The core layer has the most complete thermal conductivity network and excellent room temperature breakdown field strength, but the interlayer stress mismatch is obvious, the risk of thermal breakdown at high temperatures is relatively high, and the insulation retention rate is relatively low.

[0016] Among them, the 2-6-2 ratio has a moderate gradient and a balanced mechanical and electrical performance, making it a transitional solution.

[0017] Among them, the 3-4-3 ratio has the smallest interlayer concentration gradient (difference of only 1 wt%), the structure is closest to a uniform distribution, the best electric field homogenization effect in the gradual transition region, and the fewest interface defects. It also has the highest room temperature breakdown field strength, the lowest dielectric loss, and the best overall room temperature insulation performance.

[0018] Among them, the 4-2-4 ratio has the highest BN content in the surface layer (4 wt%) and the lowest in the core layer (2 wt%), resulting in the most uniform overall BN distribution. The surface layer exhibits the strongest corrosion resistance and heat dissipation capacity, the lowest thermal stress at high temperatures, and the best high-temperature insulation retention and corona resistance life.

[0019] Furthermore, the processing parameters of the nitrogen low-temperature plasma are: radio frequency power 100~300 W, cavity pressure 10~50 Pa, and processing time 10~60 min; amino and imino polar groups are introduced on the surface of the modified boron nitride.

[0020] Furthermore, the polyimide (PI) matrix is ​​prepared by in-situ polycondensation and thermal imidization of 4,4'-diaminodiphenyl ether (ODA) and pyromellitic dianhydride (PMDA). The molar ratio of dianhydride to diamine is 1.00~1.05:1, ensuring high molecular weight and intrinsic insulating properties of the matrix. The total thickness of the composite film is 20μm-50μm, with a three-layer thickness ratio of 1:1:1, and the symmetrical structure avoids thermal stress mismatch.

[0021] The composite film of the present invention has a DC characteristic breakdown field strength at room temperature ≥600 kV / mm and a DC characteristic breakdown field strength at 150 ℃ ≥500 kV / mm; the composite film has a corona resistance lifetime of 7.3±0.9 minutes at 150 ℃ and 3000V, which is 4.56 times and 1.24 times that of pure polyimide and unmodified composite film, respectively.

[0022] Another object of the present invention is to provide a method for preparing the above-mentioned composite film.

[0023] A method for preparing a plasma interface-controlled hierarchical corona-resistant polyimide gradient composite film includes the following steps: Step 1: Spread hexagonal boron nitride powder on the sample stage of the plasma reaction chamber, evacuate the vacuum chamber, introduce high-purity nitrogen gas, maintain the set gas pressure and radio frequency power to perform low-temperature plasma treatment, etch micro-nano structures on the filler surface and introduce nitrogen-containing polar groups to obtain modified boron nitride. Step 2: Disperse the modified boron nitride in N,N-dimethylacetamide solvent and sonicate to form a uniform suspension; add 4,4'-diaminodiphenyl ether under ice-water bath and nitrogen protection conditions until completely dissolved, add pyromellitic dianhydride in batches to carry out in-situ polycondensation reaction, and prepare polyamic acid solutions with different boron nitride mass fractions. After vacuum degassing, seal for later use. Step 3: Using an automated coating process, the lower surface layer adhesive, the core layer adhesive, and the upper surface layer adhesive are sequentially coated on a clean substrate. After each layer is coated, the substrate is pre-cured by step-by-step heating to obtain a graded corona-resistant polyimide gradient composite film. Step 4: The precursor film is subjected to high-temperature thermal imidization with programmed heating to completely dehydrate and cyclize the polyamic acid. After cooling in the furnace, the film is demolded and dried to obtain a gradient composite insulating film with three-level protection effect.

[0024] Furthermore, the heating program for the step-by-step pre-curing described in step 3 is as follows: 80 ℃ for 2 hours, 120 ℃ for 1 hour, and 170 ℃ for 1 hour.

[0025] Furthermore, the heating program for thermal imidization in step 4 is as follows: hold at 210 ℃ for 1 h, hold at 250 ℃ for 1 h, hold at 300 ℃ for 1 h, hold at 350 ℃ for 1 h, and control the heating rate at 3~5 ℃ / min.

[0026] Based on specific embodiments, the preparation method of the plasma interface-controlled hierarchical corona-resistant polyimide gradient composite film of the present invention is carried out according to the following steps: Step (1) Nitrogen plasma interface control of boron nitride: BN powder is evenly spread on the sample stage of the plasma reaction chamber, vacuumed to below 10 Pa, high-purity nitrogen is introduced to the set pressure of 10~50 Pa, the radio frequency power supply is turned on, the power is controlled at 100~300 W, and the treatment is carried out for 5~30 min; after the treatment is completed, it is taken out and sealed for storage to obtain modified BN with micro-nano etching on the surface and containing polar groups. Step (2) Preparation of gradient concentration polyamic acid adhesive: Weigh the modified BN according to the designed ratio and add it to N,N-dimethylacetamide (DMAc) solvent. Disperse it ultrasonically for 1 hour to form a uniform suspension. Transfer the suspension to a three-necked flask and add ODA under the protection of nitrogen in an ice-water bath (0~5℃). Stir until completely dissolved. Add PMDA in 3~5 batches and stir continuously for 6~8 hours to carry out in-situ polycondensation. Prepare six polyamic acid (PAA) adhesives with BN mass fractions of 1 wt%, 2 wt%, 3 wt%, 4 wt%, 6 wt%, and 8 wt%. Degas at room temperature under vacuum for 1 hour and then seal for later use. Step (3) Layer-by-layer coating and step-by-step pre-curing: The lower surface layer, core layer and upper surface layer of adhesive are coated sequentially on a clean glass plate using an automatic coating device. By combining different concentrations of adhesive, four gradient precursors, namely 1-8-1, 2-6-2, 3-4-3 and 4-2-4, are obtained respectively. After each layer is coated, step-by-step pre-curing is carried out according to the procedure of 80 ℃ / 2 h → 120 ℃ / 1 h → 170 ℃ / 1 h. By controlling the heat preservation time of 170 ℃, the diffusion degree of PAA molecules between layers is regulated, which ensures the formation of a gradual concentration transition zone and avoids excessive interlayer mutual solubility that destroys the gradient structure. Step (4) High-temperature thermal imidization and post-treatment: After the three-layer coating pre-curing is completed, the temperature is increased at a rate of 3-5 ℃ / min, and thermal imidization is completed sequentially at 210 ℃ / 1 h, 250 ℃ / 1 h, 300 ℃ / 1 h, and 350 ℃ / 1 h; after the furnace is naturally cooled to room temperature, the glass plate is immersed in deionized water to remove the film, and vacuum dried at 60 ℃ for 2 h to obtain the finished film.

[0027] Compared with the prior art, the present invention has the following beneficial effects: To overcome the problems of insufficient insulation performance of polyimide-based composite films in the prior art due to poor interfacial bonding, abrupt changes in gradient structure, and lack of quantitative basis for concentration ratio, this invention provides a polyimide-based composite film and its preparation method. Through interfacial strengthening, gradual gradient structure design, and concentration ratio optimization, it achieves a synergistic improvement in insulation breakdown field strength, corona resistance life, and high-temperature stability.

[0028] This invention employs nitrogen-based low-temperature plasma to modify the surface of hexagonal boron nitride (BN) filler. This process physically etches the BN surface while introducing polar groups, thereby upgrading the original weak van der Waals forces between the filler and the PI matrix into a strong interfacial bond combining physical intercalation and chemical bonding. This interface strengthening mechanism effectively suppresses the accumulation of space charge at the interface, alleviates local electric field distortion, and thus improves the insulation reliability of the composite film.

[0029] In terms of structural design, this invention breaks through the gradient design concept of concentration-abrupt layered stacking in existing technologies. It adopts a segmented pre-curing process to induce inter-layer molecular diffusion, naturally forming a gradually changing transition region with continuous concentration variation. This transition region enables the dielectric constant of the composite film to smoothly transition along the thickness direction, eliminating the electric field concentration effect caused by abrupt changes in the interlayer dielectric constant. This allows the electric field homogenization function of the gradient structure to be fully utilized, simultaneously improving the breakdown field strength and high-temperature stability of the material.

[0030] For the symmetrical sandwich structure of "surface-core-surface", this invention systematically designed four typical concentration ratios, namely, the BN content ratio of the surface layer to the core layer is 1:8:1, 2:6:2, 3:4:3, and 4:2:4, respectively. Based on experimental studies of the above ratio systems, this invention clarified the following pattern: corona resistance lifetime is positively correlated with the surface layer BN content, while breakdown uniformity is negatively correlated with the interlayer concentration gradient. This quantitative pattern provides data support for material selection under different service conditions.

[0031] Based on the aforementioned interface reinforcement and gradient-variable structure, this invention establishes a three-tiered protection mechanism: "surface self-barrier corrosion resistance—transition zone buffering electric field distortion—core layer uniform field heat conduction." Specifically, the surface layer achieves a self-barrier function against corona erosion through BN enrichment; the transition zone buffers electric field stress, blocking the propagation of electrical trees along the interface direction; and the core layer, through a BN network, blocks the longitudinal extension of electrical trees while simultaneously achieving uniform field strength distribution and rapid heat conduction.

[0032] The nitrogen low-temperature plasma modification method used in this invention is a dry processing technique that is environmentally friendly and highly efficient. The overall preparation process is compatible with existing industrial coating processes for PI films, and the aforementioned performance improvements can be achieved with only a three-layer structure, eliminating the need for complex multi-layer stacking processes and demonstrating good applicability for large-scale production.

[0033] For a deeper understanding of the features and technical content of this invention, please refer to the accompanying detailed description and drawings. It should be noted that the drawings are provided for illustrative purposes only and are not intended to limit the scope of the invention. Attached Figure Description

[0034] Figure 1 X-ray diffraction patterns before and after boron nitride modification; Figure 2 Scanning electron microscope images before and after boron nitride modification; Figure 3 Fourier transform infrared spectra of dielectric thin films in Examples 1-4 and Comparative Examples 1-3; Figure 4 X-ray diffraction patterns of dielectric thin films in Examples 1-4 and Comparative Examples 1-3; Figure 5 The graphs show the room temperature relative permittivity properties of the dielectric thin films in Examples 1-4 and Comparative Examples 1-3. Figure 6 The following are the room temperature dielectric loss factor diagrams for dielectric thin films in Examples 1-4 and Comparative Examples 1-3; Figure 7 These are the room temperature breakdown field strength diagrams for dielectric thin films in Examples 1-4 and Comparative Examples 1-3; Figure 8 These are breakdown field strength diagrams of dielectric films in Examples 1-4 and Comparative Examples 1-3 at 100°C. Figure 9 These are breakdown field strength diagrams of dielectric films in Examples 1-4 and Comparative Examples 1-3 at 150°C. Figure 10 This is a comparison chart of the comprehensive breakdown field strength performance of dielectric thin films in Examples 1-4 and Comparative Examples 1-3; Figure 11 The following are room temperature corona resistance lifetime diagrams for dielectric films in Examples 1-4 and Comparative Examples 1-3; Figure 12Corona resistance lifetime of dielectric films in Examples 1-4 and Comparative Examples 1-3 at 100°C; Figure 13 Corona resistance lifetime of dielectric films in Examples 1-4 and Comparative Examples 1-3 at 150°C; Figure 14 The graph shows a comparison of the breakdown field strength, corona resistance, and lifetime of dielectric films in Examples 1-4 and Comparative Examples 1-3. Detailed Implementation

[0035] The present invention will be described in detail below with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but should not be considered as limiting the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0036] Example 1: 1-8-1 gradient composite film (PI / PBN-181) BN plasma modification: Hexagonal BN powder was spread evenly in the plasma reaction chamber, evacuated to 8 Pa, and high-purity nitrogen was introduced to 20 Pa. The radio frequency power was 200 W, and the treatment was carried out for 10 min, 20 min, 40 min and 60 min respectively to obtain modified BN, denoted as PBN.

[0037] Preparation of adhesive solution: PAA / PBN adhesive solutions with BN mass fractions of 1 wt% and 8 wt% were prepared respectively: the modified BN was weighed according to the formula and added to DMAc, and ultrasonically dispersed for 1 h; 3g of ODA was added under ice water bath and stirred to dissolve, and a total of 3.28g of PMDA was added in 4 batches and stirred for 7 h to obtain a viscous adhesive solution, and vacuum degassed at room temperature for 1 h.

[0038] Layer-by-layer coating and curing: 1 wt% adhesive solution (lower surface layer), 8 wt% adhesive solution (core layer), and 1 wt% adhesive solution (upper surface layer) are applied sequentially. After each layer is applied, pre-curing is performed at 80 ℃ / 2 h → 120 ℃ / 1 h → 170 ℃ / 1 h. Finally, the temperature is increased to 350 ℃ to complete thermal imidization, followed by cooling, demolding, and drying to obtain a three-layer composite film with a total thickness of approximately 30 μm and a gradual transition zone thickness of approximately 1.2 μm between layers.

[0039] Example 2: 2-6-2 gradient composite film (PI / PBN-262) The only difference between this embodiment and Example 1 is that the surface layer BN mass fraction is 2 wt% and the core layer BN mass fraction is 6 wt%. The remaining preparation steps and parameters are exactly the same as in Example 1.

[0040] Example 3: 3-4-3 gradient composite film (PI / PBN-343) The only difference between this embodiment and Example 1 is that the surface layer BN mass fraction is 3 wt% and the core layer BN mass fraction is 4 wt%. The remaining preparation steps and parameters are exactly the same as in Example 1.

[0041] Example 4: 4-2-4 gradient composite film (PI / PBN-424) The only difference between this embodiment and Embodiment 1 is that the surface layer BN mass fraction is 4 wt% and the core layer BN mass fraction is 2 wt%. The remaining preparation steps and parameters are exactly the same as in Embodiment 1.

[0042] Comparative Example 1: Pure PI film In this comparative example, no BN filler was added, and the remaining preparation steps and parameters were exactly the same as in Example 1.

[0043] Comparative Example 2: Unmodified BN three-layer gradient film (PI / BN-424) In this comparative example, unmodified raw BN powder was used, and the formulation and preparation process were the same as in Example 3.

[0044] Comparative Example 3: Monolayer Uniformly Doped PI / BN Thin Film In this comparative example, the total mass fraction of BN is the same as in Example 3 (approximately 3.33 wt%), and it is prepared using a single-layer, one-time coating process. The remaining steps and parameters are the same as in Example 1.

[0045] X-ray diffraction patterns before and after boron nitride modification are as follows: Figure 1As shown in the XRD pattern, no additional impurity peaks appeared in the modified sample, indicating that the structural homogeneity of BN was maintained during plasma treatment and no other phases were introduced. Notably, the intensity of the 002 crystal plane diffraction peaks in PBN-40m was significantly enhanced compared to the original BN. This enhancement stems from the plasma-induced removal of the disordered surface layer, allowing the underlying 002 crystal planes to be more fully exposed, thereby increasing the 002 / 100 peak intensity ratio. The higher 002 / 100 ratio indicates improved interlayer ordering in the modified BN, implying improved compatibility between the filler and the polymer matrix. Furthermore, the enhanced 002 peaks also reflect the increased crystallinity of BN after plasma treatment. Since boron nitride (BN) is a wide-bandgap inorganic insulator, higher crystallinity helps it block charges more effectively. This enhancement stems from plasma-induced removal of the disordered surface layer, allowing the underlying 002 crystal planes to be more fully exposed, thereby increasing the 002 / 100 peak intensity ratio. A higher 002 / 100 ratio indicates improved interlayer ordering in the modified BN, implying improved compatibility between the filler and the polymer matrix. Furthermore, the enhanced 002 peak also reflects the increased crystallinity of BN after plasma treatment; therefore, the subsequently selected modified boron nitride (PBN) was BN modified for 40 minutes.

[0046] Scanning electron microscope images of BN before and after modification are shown below. Figure 2 As shown in the figure, the modified boron nitride exhibits higher uniformity and significantly reduced agglomeration, which indirectly demonstrates the superiority of modification for boron nitride surface treatment.

[0047] Fourier transform infrared spectra of dielectric thin films in Examples 1-4 and Comparative Examples 1-3 are shown below. Figure 3 As shown, all samples fully exhibited the typical characteristic absorption peak of polyimide: approximately 1778 cm⁻¹. -1 The corresponding asymmetric stretching vibration of the imide ring C=O is approximately 1716 cm⁻¹. -1 The corresponding symmetric stretching vibration of the imide ring C=O is located at approximately 1375 cm⁻¹. -1 The stretching vibration of the CN bond in the imide ring is located at approximately 726 cm⁻¹. -1 The corresponding out-of-plane bending vibration of the imide ring is located at approximately 1502 cm. -1The peaks exhibited indicate the stretching vibrations of the benzene ring skeleton. The presence of these characteristic peaks suggests that the polyamic acid precursor has undergone sufficient imidization after the stepwise coating and thermal imidization processes, forming a stable polyimide crosslinked matrix structure. The multilayer coating process did not damage the chemical structure of the polyimide. Comparing the composite films prepared with unmodified boron nitride and modified boron nitride, the peak positions of the polyimide characteristic peaks and the boron nitride characteristic peaks showed no significant shift, indicating that the filler modification treatment did not destroy the intrinsic crystal structure of boron nitride, nor did it alter the main chain chemical structure of the polyimide matrix.

[0048] X-ray diffraction patterns of dielectric thin films in Examples 1-4 and Comparative Examples 1-3 are shown below. Figure 4 As shown, the pure PI film exhibits broad, diffuse diffraction peaks in the 10°–30° range, without sharp crystalline phase diffraction peaks. This indicates that the pure polyimide prepared in this invention has a typical amorphous structure, consistent with the intrinsic structural characteristics of aromatic polyimides, proving that the thermal imidization process did not induce additional crystallization in the polyimide backbone. All boron nitride-doped composite films show sharp, symmetrical characteristic diffraction peaks at approximately 26.7°, corresponding to the (002) crystal plane characteristic diffraction of hexagonal boron nitride; simultaneously, a weak (004) crystal plane diffraction peak can be observed at approximately 55°. This result directly confirms that after the entire process of precursor mixing, stepwise coating, and thermal imidization, the boron nitride filler still maintains a complete hexagonal crystalline phase structure, and the preparation process did not destroy the intrinsic crystalline framework of the filler. Furthermore, with the increase of boron nitride doping ratio, the intensity of the (002) crystal plane diffraction peaks increased regularly, and the peak shape remained sharp without significant broadening or peak position shift. This indicates that boron nitride maintained its original crystallinity under different doping amounts, and no additional by-products were generated in the composite system, indicating good structural compatibility between the matrix and the filler. Comparing the unmodified boron nitride composite sample (PI / BN-424) and the modified boron nitride composite sample (PI / PBN-424), the peak positions and shapes of the characteristic diffraction peaks were basically the same, indicating that plasma surface modification only modulates the surface chemical properties of the filler and does not change the bulk crystal structure of boron nitride, which is consistent with the aforementioned infrared spectral analysis results.

[0049] The room temperature relative permittivity performance graphs of dielectric thin films in Examples 1-4 and Comparative Examples 1-3 are shown below. Figure 5As shown, the dielectric constant of most samples remained stable across the entire test frequency range, with only a slight decrease in the high-frequency range, exhibiting good frequency stability. This indicates weak interfacial polarization within the film and effective suppression of space charge accumulation. The relative dielectric constant of the PI / PBN-181 sample was significantly higher than that of the other modified composite samples. This is due to the large difference in boron nitride doping concentration between the surface and core layers, resulting in a higher degree of compositional abrupt change at the interlayer interface, leading to a stronger interfacial polarization effect and ultimately an increase in the overall dielectric constant. This result directly confirms that the interlayer concentration gradient is a key factor in regulating the dielectric insulation performance of composite films. The relative dielectric constant is a core parameter for evaluating the electrical performance of insulating materials. A lower dielectric constant can effectively suppress electric field distortion at the electrode-dielectric interface, increase the partial discharge initiation voltage, reduce dielectric loss and Joule heating under AC electric fields, and reduce insulation degradation caused by local space charge accumulation. This improves the long-term insulation reliability of the material from multiple dimensions, including electric field homogenization, thermal aging suppression, and charge blocking. Compared with the sample prepared with unmodified filler, the three-layer composite film prepared by plasma-modified boron nitride exhibits superior frequency stability of dielectric constant. This is attributed to the modification treatment, which improves the interfacial bonding between the filler and the polyimide matrix and reduces interfacial defects. Furthermore, by rationally controlling the interlayer filler concentration ratio of the three-layer structure, this invention can maintain the dielectric constant at a low level while introducing boron nitride filler to improve corona resistance. This avoids the problem of dielectric performance deterioration caused by traditional doping modification and large concentration difference layer structures, achieving a synergistic improvement in corona resistance and insulation performance. Moreover, the dielectric performance can be controlled and adjusted by adjusting the filler doping ratio and layer thickness ratio.

[0050] The room temperature dielectric loss factor diagrams for dielectric thin films in Examples 1-4 and Comparative Examples 1-3 are shown below. Figure 6 As shown, the dielectric loss factor of all samples exhibits a trend of first decreasing and then increasing with increasing frequency, reaching a certain level at 10... 2 ~10 3The loss factor reaches its lowest value in the Hz range. In the low-frequency range, the loss is mainly dominated by conductivity loss and slow interface polarization, while the increase in high-frequency loss is due to the dipole polarization response lagging behind the electric field alternation. The dielectric loss factor of the PI / PBN-181 sample is significantly higher than that of other modified composite samples in the low-frequency range. This is because the difference in boron nitride doping concentration between the surface and core layers of this sample is too large, resulting in a higher degree of compositional abruptness at the interlayer interface, leading to stronger interface polarization and interface conductivity effects, ultimately causing an increase in the overall loss level of the system. This further confirms that the interlayer concentration gradient is a key factor in regulating the dielectric insulation performance of the composite film. Compared with the PI / BN-424 sample prepared with unmodified boron nitride, the PI / PBN-424 sample prepared with plasma-modified boron nitride has a lower dielectric loss level, thanks to the plasma modification optimizing the filler and polyimide group. The interfacial bonding state of the body reduces interfacial voids and defect states, suppressing interfacial polarization and carrier scattering losses. Overall, the modified three-layer composite film with reasonable interlayer ratio design maintains a low dielectric loss level, which is on the same order of magnitude as that of pure polyimide matrix. This indicates that the sandwich structure design and plasma filler modification synergistic scheme of the present invention can effectively control the growth of dielectric loss while introducing boron nitride filler to improve corona resistance. It avoids the drawback of traditional doping modification that easily leads to a significant increase in dielectric loss, reduces Joule heating and thermal aging rate of materials under long-term AC electric field service, and thus significantly improves the operational reliability and service life of insulating materials.

[0051] The room temperature breakdown field strength diagrams of dielectric thin films in Examples 1-4 and Comparative Examples 1-3 are shown below. Figure 7 As shown, the field strength value corresponding to a breakdown probability of 63.2% is taken as the characteristic breakdown field strength of each sample. E b Among the samples, the two groups with excessively large differences in filler concentration between the surface and core layers exhibited lower characteristic breakdown field strengths than the pure polyimide matrix. This was due to the excessively high degree of abrupt change in interlayer composition, which introduced more interface defects and electric field concentration sites, accelerating the initiation and propagation of electrical trees, ultimately leading to a decrease in breakdown performance. This aligns with the aforementioned changes in dielectric constant and dielectric loss. The composite film modified with plasma filler and matched with a reasonable interlayer concentration ratio showed a significant improvement in characteristic breakdown field strength compared to both the pure polyimide and unmodified filler composite samples. The optimal sample showed a 20.7% increase in characteristic breakdown field strength compared to pure polyimide. This is attributed to the fact that plasma modification improved the interfacial bonding between the filler and the polyimide matrix, reducing interface voids and other defects. Simultaneously, the sandwich structure, through the homogenization of the interfacial electric field and the blocking of space charge injection in the surface layer, synergistically works with the corona resistance function of the core layer, effectively suppressing the formation and propagation of breakdown channels and achieving significant optimization of insulation breakdown performance.

[0052] The breakdown field strength diagrams of dielectric films in Examples 1-4 and Comparative Examples 1-3 at 100°C are shown below. Figure 8As shown, with increasing test temperature, the characteristic breakdown field strength of all samples decreased to varying degrees compared to room temperature. This is due to the intensified thermal motion of the polyimide molecular chains at high temperatures, which increases the thermally excited carrier mobility and makes it easier to induce carrier collisional ionization and breakdown channel expansion. Among them, the two groups of samples with excessively large differences in filler concentration between the surface and core layers still had inferior breakdown performance compared to the pure polyimide matrix. However, the composite film modified with plasma filler and matched with a reasonable interlayer ratio maintained the highest characteristic breakdown field strength at 100℃, which was significantly better than the composite sample of pure polyimide and unmodified filler. This indicates that the structural design can still effectively play the role of interface optimization and electric field homogenization under medium temperature conditions, maintaining better insulation reliability.

[0053] The breakdown field strength diagrams of dielectric films in Examples 1-4 and Comparative Examples 1-3 at 150°C are shown below. Figure 9 As shown, with further increases in test temperature, the characteristic breakdown field strength of all samples continued to decrease. The high-temperature thermal effect intensified the relaxation motion of molecular chains and the thermal excitation process of charge carriers, resulting in a further decrease in the overall insulation withstand capability of the material. At a high temperature of 150℃, the plasma-modified optimal ratio three-layer composite film still maintained the highest breakdown field strength, exhibiting a significant performance advantage over the pure polyimide matrix. However, the breakdown performance of samples with excessive interlayer concentration differences remained at a low level. This trend is consistent with the test results at room temperature and 100℃, demonstrating that the structural modification scheme of this invention has good temperature adaptability in improving insulation performance and can meet the insulation application requirements under wide temperature range conditions.

[0054] The comparison diagram of the comprehensive breakdown field strength of dielectric thin films in Examples 1-4 and Comparative Examples 1-3 is shown below. Figure 10 As shown, overall, the breakdown field strength of all three groups of samples gradually decreased with increasing temperature. A horizontal comparison reveals that the breakdown field strength of the unmodified boron nitride composite film was slightly higher than that of pure polyimide at all temperatures, while the plasma-modified sandwich structure composite film exhibited significantly higher breakdown field strength than the other two groups across the entire test temperature range, maintaining a considerable performance improvement even at high temperatures. These results clearly demonstrate that the synergistic design of plasma filler modification and the sandwich structure not only improves insulation breakdown performance at room temperature but also effectively suppresses insulation performance degradation at high temperatures, significantly broadening the material's applicable temperature range and enhancing operational reliability in high-temperature service scenarios.

[0055] The room temperature corona resistance lifetime diagrams of dielectric films in Examples 1-4 and Comparative Examples 1-3 are shown below. Figure 11As shown, the corona resistance lifetime of pure polyimide film was 4.9 ± 0.9 min. After introducing boron nitride functional filler, the corona resistance performance of the composite films was improved to varying degrees. Among them, the sample prepared by plasma-modified boron nitride with a reasonable interlayer concentration ratio showed the best corona resistance lifetime, reaching 14.0 ± 1.2 min, which is about 1.9 times higher than that of pure polyimide. The core mechanism of performance improvement lies in the fact that the plate-like structure of hexagonal boron nitride can form a physical barrier, bending and extending the propagation path of electrical trees. At the same time, its excellent thermal conductivity can quickly dissipate the local Joule heat generated by corona discharge, inhibiting the thermo-electric synergistic degradation. Plasma surface modification strengthens the interfacial bonding between the filler and the polyimide matrix, reduces interfacial voids and defect states, and avoids local electric field concentration that accelerates corona erosion. The improvement in corona resistance was limited for samples with excessively large differences in interlayer filler concentration, and the corona resistance lifetime of the composite sample prepared by the unmodified filler was also lower than that of the modified sample with the same ratio, which is consistent with the aforementioned variation law of dielectric and breakdown properties.

[0056] Examples 1-4 and Comparative Examples 1-3 show the corona resistance lifetime of the dielectric films at 100°C. Figure 12 As shown, due to the intensified thermal motion of polyimide molecular chains at high temperatures and the synergistic enhancement of the chemical erosion and thermal aging effects of corona discharge, the corona resistance lifetime of all samples decreased to varying degrees compared to room temperature. The corona resistance lifetime of pure polyimide film decreased to 3.8 ± 0.4 min, with a decrease of approximately 22.4%; while the optimally proportioned three-layer composite film modified by plasma still achieved a corona resistance lifetime of 13.6 ± 0.6 min, only decreasing by about 2.9% compared to room temperature, and was 3.6 times that of pure polyimide at the same temperature. These results indicate that the high thermal conductivity of boron nitride filler can effectively reduce the local hot spot temperature under high-temperature corona conditions, weakening the destructive effect of thermal aging on the matrix; at the same time, the stable interface constructed by plasma modification can still maintain good structural integrity at 100℃, avoiding defect expansion caused by interfacial thermal relaxation, thus maintaining excellent corona resistance stability in a medium-temperature environment.

[0057] Examples 1-4 and Comparative Examples 1-3 show the corona resistance lifetime of the dielectric films at 150°C. Figure 13As shown, with further increases in test temperature, the relaxation degree of polyimide molecular chains significantly increases, and the synergistic degradation effect of corona discharge and thermal aging is further enhanced, resulting in a continuous decrease in the corona resistance lifetime of all samples. The corona resistance lifetime of pure polyimide film is only 1.6±0.6 min, which is insufficient to maintain effective insulation function; while the optimal ratio three-layer composite film modified by plasma still achieves a corona resistance lifetime of 7.3±0.9 min, which is 4.56 times that of pure polyimide at the same temperature, demonstrating a significant advantage in high-temperature corona resistance. This is because the thermally conductive network constructed by high-content boron nitride filler can quickly dissipate the heat generated by the combined effects of high temperature and corona discharge, inhibiting the thermal decomposition of matrix molecular chains and the accelerated propagation of electrical trees; at the same time, the gradient design of the sandwich structure and the synergistic effect of the modified interface can effectively block space charge injection and the propagation of electrical trees into the core layer, thereby maintaining a higher corona resistance lifetime even at a high temperature of 150℃.

[0058] Comparison charts of breakdown field strength, corona resistance, and lifetime of dielectric thin films in Examples 1-4 and Comparative Examples 1-3 Figure 14 As shown, overall, the corona resistance lifetime of all three groups of samples decreased with increasing ambient temperature, but the rate of performance degradation differed significantly: the corona resistance lifetime of pure polyimide decreased most drastically with increasing temperature, retaining only about 32.7% of the room temperature level at 150℃; the degradation rate of the unmodified boron nitride composite film was somewhat narrowed; while the plasma-modified three-layer composite film exhibited the best temperature stability in corona resistance performance, retaining over 97% of its performance at 100℃ and still retaining more than 50% of the room temperature level at 150℃. These results fully demonstrate that the synergistic design of plasma filler surface modification and the sandwich layered structure not only improves corona resistance performance at room temperature but also significantly inhibits insulation degradation caused by electro-thermal synergy at high temperatures, greatly enhancing the high-temperature corona resistance stability and wide-temperature-range applicability of the material. This effectively meets the application requirements for high-temperature corona resistance performance of insulating materials in fields such as new energy power generation and high-speed motors.

[0059] The specific embodiments of the present invention have been described in detail above. It should be noted that the present invention is not limited to the specific embodiments described above. Various modifications or alterations can be made by those skilled in the art without departing from the scope of protection defined by the claims, and all such modifications or alterations fall within the scope of the present invention.

Claims

1. A plasma interface-controlled hierarchical corona-resistant polyimide gradient composite film, characterized in that, The composite film has a three-layer symmetrical gradient structure, consisting of an upper surface layer, a core layer, and a lower surface layer that are tightly bonded together in sequence. The upper and lower surface layers have the same composition and thickness, and are both polyimide matrices doped with plasma-modified boron nitride. The core layer is a polyimide matrix doped with plasma-modified boron nitride. The boron nitride mass fraction is symmetrically gradient distributed along the thickness direction of the film, and a gradually changing transition region with continuously varying boron nitride concentration is formed between the surface layer and the core layer.

2. The graded corona-resistant polyimide gradient composite film according to claim 1, characterized in that, The thickness of the gradually changing transition region is 0.5~2µm, accounting for 5%~10% of the corresponding single-layer thickness.

3. The graded corona-resistant polyimide gradient composite film according to claim 1, characterized in that, The boron nitride mass fraction in the upper and lower surface layers is 1 wt%-4 wt%; the boron nitride mass fraction in the core layer is 2 wt%-8 wt%; and the difference in boron nitride mass fraction between the surface layer and the core layer is 1 wt%-7 wt%.

4. The graded corona-resistant polyimide gradient composite film according to claim 3, characterized in that, The mass fraction ratio of the interlayer of the composite film is one of four gradients: surface layer-core layer-surface layer = 1-8-1, 2-6-2, 3-4-3, and 4-2-4.

5. The graded corona-resistant polyimide gradient composite film according to claim 1, characterized in that, The plasma-modified boron nitride is a hexagonal boron nitride nanosheet treated with nitrogen low-temperature plasma. The treatment parameters of the nitrogen low-temperature plasma are: radio frequency power 100~300 W, cavity pressure 10~50 Pa, and treatment time 10~60 min.

6. The graded corona-resistant polyimide gradient composite film according to claim 1, characterized in that, The polyimide matrix is ​​prepared by in-situ polycondensation and thermal imidization reaction of 4,4'-diaminodiphenyl ether and pyromellitic dianhydride, with a molar ratio of dianhydride to diamine of 1.00~1.05:1; the total thickness of the composite film is 20µm~50µm, and the thickness ratio of the upper surface layer, core layer and lower surface layer is 1:1:

1.

7. The graded corona-resistant polyimide gradient composite film according to claim 1, characterized in that, The composite film has a room temperature DC characteristic breakdown field strength ≥600 kV / mm and a high temperature DC characteristic breakdown field strength ≥500 kV / mm at 150 ℃; the composite film has a corona resistance lifetime of 7.3±0.9 minutes at 150℃ and 3000V.

8. A method for preparing a plasma interface-controlled hierarchical corona-resistant polyimide gradient composite film as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1: Spread hexagonal boron nitride powder on the sample stage of the plasma reaction chamber, evacuate the vacuum chamber, introduce high-purity nitrogen gas, maintain the set gas pressure and radio frequency power to perform low-temperature plasma treatment, etch micro-nano structures on the filler surface and introduce nitrogen-containing polar groups to obtain modified boron nitride. Step 2: Disperse the modified boron nitride in N,N-dimethylacetamide solvent and sonicate to form a uniform suspension; add 4,4'-diaminodiphenyl ether under ice-water bath and nitrogen protection conditions until completely dissolved, add pyromellitic dianhydride in batches to carry out in-situ polycondensation reaction, and prepare polyamic acid solutions with different boron nitride mass fractions. After vacuum degassing, seal for later use. Step 3: Using an automated coating process, the lower surface layer adhesive, the core layer adhesive, and the upper surface layer adhesive are sequentially coated on a clean substrate. After each layer is coated, the substrate is pre-cured by step-by-step heating to obtain a graded corona-resistant polyimide gradient composite film. Step 4: The precursor film is subjected to high-temperature thermal imidization with programmed heating to completely dehydrate and cyclize the polyamic acid. After cooling in the furnace, the film is demolded and dried to obtain a gradient composite insulating film with three-level protection effect.

9. The preparation method according to claim 8, characterized in that, The step-by-step pre-curing temperature program described in step 3 is as follows: 80 ℃ for 2 hours, 120 ℃ for 1 hour, and 170 ℃ for 1 hour.

10. The preparation method according to claim 8, characterized in that, The heating program for thermal imidization in step 4 is as follows: hold at 210 ℃ for 1 h, hold at 250 ℃ for 1 h, hold at 300 ℃ for 1 h, and hold at 350 ℃ for 1 h, with the heating rate controlled at 3~5 ℃ / min.